Working guide to petroleum and natural gas production engineering - Lyons, William C. (Amsterdam ; Boston : Gulf Pub./Elsevier, 2010)
Covers properties of hydrocarbon mixtures, flow natural flow of fluids, natural flow performance, artificial lift methods and corrosion and scaling. This book provides engineers with a basis for understanding important concepts such a flow phenomena, hydrate formation, pressure (surge) waves, or high viscosity liquid flow failure.
Working Guide to Petroleum and Natural Gas Production Engineering provides an introduction to key concepts and processes in oil and gas production engineering. It begins by describing correlation and procedures for predicting the physical properties of natural gas and oil. These include compressibility factor and phase behavior, field sampling process and laboratory measurements, and prediction of a vapor-liquid mixture. The book discusses the basic parameters of multiphase fluid flow, various flow regimes, and multiphase flow models. It explains the natural flow performance of oil, gas, and the mixture. The final chapter covers the design, use, function, operation, and maintenance of oil and gas production facilities; the design and construction of separators; and oil and gas separation and treatment systems.
Front Cover; Working Guide to Petroleum and Natural Gas Production Engineering; Copyright; Full Contents; Chapter 1. Properties of Hydrocarbon Mixtures; 1.1. Compressibility Factor and Phase Behavior; 1.2. Sampling Process and Laboratory Measurements; 1.3. Vapor-Liquid Equilibrium by Equation of State; References; Chapter 2. Flow of Fluids; 2.1. Basic Parameters of Multiphase Flow [1]; 2.2. Slightly Inclined Pipes ( -10 <<U+006b><15); 2.3. Risers and Wells (<U+006b>=90); 2.4. Downcomers (<U+006b>=-90); 2.5. Stratified Flow Regime; 2.6. Annular Flow Regime; 2.7. Slug Flow Regime; 2.8. Bubby Flow Regime. 2.9. Correction for Acceleration Effects2.10. Limitation; 2.11. Empirical Methods; 2.12. The Duns-Ros Method [20, 21]; 2.13. The Orkiszewski Method [8, 9]; 2.14. The Hagedorn-Brown Method [9, 12, 13]; 2.15. The Beggs-Brill Method [2, 9, 15]; 2.16. Mechanistic Models; 2.17. Hasan and Kabir Model [18, 19]; 2.18. Summary; References; Chapter 3. Natural Flow Performance; 3.1. Inflow Performance; 3.2. Two-Phase Flow Performance; References; Chapter 4. Gas Production Engineering; 4.1. Surface Production/Separation Facility; 4.2. Pressure Vessel Relief Systems; 4.3. Separator Design and Construction. 4.4. Vertical Separators4.5. Horizontal Separator; 4.6. Vessel Internals [18]; 4.7. Oil-Water-Gas Separation; 4.8. Two-Stage Separation Systems; 4.9. Crude Oil Treating Systems; References; Index.
Includes bibliographical references and index.
Keywords: Petroleum engineering; Natural gas